Expression of the apoptosis repressor with caspase recruitment domain (ARC) in liver metastasis of colorectal cancer and its correlation with DNA mismatch repair proteins and p53 - Tóth, Csaba; Herpel, Esther; Schirmacher, Peter (Journal of cancer research and clinical oncology, 2016)
IntroductionApoptotic signaling is one of the most important processes in the measurement of chemotherapeutic effectiveness. In apoptotic machinery, various pathways and proteins are involved (i.e., mismatch repair proteins, p53). One of the regulatory proteins is ARC, which can inhibit not only the extrinsic but also the intrinsic apoptotic signaling.Materials and MethodsIn this study, we investigated the expression levels of ARC in colorectal liver metastasis and compared them with the expression of mismatch repair proteins and p53. Furthermore, we investigated ARC expression level depending on sex, age, tumor grade, mucin production, tumor size and number of liver metastasis.ResultsARC expression level in colorectal cancer liver metastasis was independent from clinical data (i.e., age, gender, tumor size, tumor number or mucin production) but strongly correlated with MSH2 and MSH6 expression, which further supported the evidence for the regulatory role of MSH2 and MSH6 in apoptosis; i.e., in case of sufficient MSH2 and MSH6 expression, significantly higher ARC level is required to suppress the apoptosis. A regulatory interaction between ARC and p53 has been described, but we found no correlation between p53 expression levels and ARC levels.ConclusionFurther studies are needed to define the exact role of ARC in apoptotic signaling and thus its role in chemoresistance and survival of tumor cells.